A hybrid current modulated DAB DC/DC converter for connecting PV modules to DC grid considering partial shading. (July 2022) - Zengin, Sinan
Highlights: A hybrid current modulation is proposed for DAB converter that realizes the DC grid connection of PV modules under partial shading conditions. The operation regions, modulation index ratio, transformer turns ratio, and the value of leakage inductance is assessed in detail. High voltage gain, smaller core size, and low number of semiconductors is offered by the proposed converter. Abstract: The Maximum Power Point (MPP) voltage of a PV module can decrease significantly under partial shading conditions. Hence, high voltage gain converters are required to connect PV modules to DC grid. Generally, two-stage boost-based converters are preferred for their simplicity. However, they utilize a high number of semiconductors with high withstand voltages, and require an input filter inductance. In this paper, a hybrid current modulation that uses triangular (TRM) and trapezoidal (TZM) current modulations is proposed for Dual Active Bridge (DAB) converter to connect PV modules to DC grid. The proposed converter provides soft switching, low number of semiconductors, and reduces the breakdown voltages of input semiconductors compared with the two-stage Boost Full Bridge Isolated Converter (BFBIC). It also eliminates the input inductance and uses a 36% smaller core size than the total core size of BFBIC. The proposed converter is realized by an experimental prototype, and analyses are verified. Graphical abstract: Hybrid current modulated DAB converter for connecting PV modules to DC microgrid. Image, graphical abstract